Incidence and Management of Severe Muscle and Tendon Injuries in Elite Korean Badminton Players: A Focus on Gender-Specific Patterns - Munku Song; Sangcheol Yoo; Kwangnam Kim; Chaofan Chen (운동과학)
PURPOSE Although muscle and tendon injuries are common among badminton players, there has been little research into these specific injuries. This study aimed to investigate the incidence and management practices of severe muscle and tendon injuries in a sample of elite Korean badminton players, focusing on sex differences. METHODS This study included 126 athletes aged 19–23 years with an average age of 21.1±1.4 years, providing 135 injury data points (65 male and 70 female). Participants were asked to describe their experiences with muscle and tendon injuries that limited training participation for more than one month during their athletic careers, as well as their post-injury management practices, through structured interviews. RESULTS Approximately 54% of the participants sustained at least one severe muscle or tendon injury during their athletic careers, with a reinjury rate of 56.2%. Most injuries occurred during training sessions, had a chronic onset, and were more common in the dominant limbs. Common injuries included patellar tendinopathy, Achilles tendinopathy/rupture, and calf muscle tears. Male athletes were more likely to sustain injuries from smash or stroke movements (odds ratio, OR=3.80, 95% confidence interval, CI=1.14–12.65, p=.030) than female athletes, and had a slightly higher likelihood of sustaining upper limb injuries (OR=3.55, 95% CI=0.96–13.13, p=.058). Psychological concerns following an injury were primarily related to the risk of reinjury; however, more than half of the athletes resumed training without specialized rehabilitation or medical authorization. CONCLUSIONS The study findings indicate that elite badminton players are highly susceptible to severe muscle and tendon injuries, with a significant risk of reinjury, and exhibit gender-specific patterns, emphasizing the importance of gender-specific management strategies, comprehensive rehabilitation, and medical authorization to ensure a safe return to training.